Break points in Grand Slam men's singles tennis - O'Donoghue, P. (Journal of Quantitative Analysis in Sports, 2012)
The current investigation was composed of two related studies. The aim of the first study was to compare the proportion of break points and non-break points won by players receiving serve in matches of the 2011 US Open men's singles tournament. Match statistics were recorded from the official tournament website for the 92 matches where both players had at least 5 break points. Wilcoxon signed ranks tests revealed that winning players won a significantly greater proportion of break points than non-break points (p = 0.004) while losing players won a similar proportion of break points to non-break points (p = 0.994).